Polyintentionality in educational Internet environment (based on the material of English-language TED Talks) - Bukina, Julia V.; Shiryaeva, Tatyana A. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The article provides a comprehensive analysis of the issue of intentionality in the educational Internet space and introduces the concept of “polyintentionality” as a specific characteristic of TED Talks media discourse. The aim of the article is to analyze the diversity of communicative intentions embedded in the content of educational media texts of TED Talks, including the analysis of the context types, communicative mechanisms and linguistic means that contribute to the achievement of different goals within a single speech. The authors introduce the concept of “polyintentionality” as a specific characteristic of TED Talks media discourse, distinguishing macrointentionality, which includes general goals and intentions of communicative acts, and microintentionality, which takes into account detailed intents in specific utterances. The paper pays attention to the general theoretical aspects that define ‘intention’ as an essential element shaping the speaker’s goals and motivation. The authors emphasize that video lectures on the TED platform, are characterized by heterogeneous intentionality of a complex nature. The authors distinguish four leading macrointentions in TED Talks texts: informing, persuading, inducing, inspiring and entertaining, each of which is realized through a variety of microintentions and linguistic means, both verbal and non-verbal. Based on a quantitative analysis of the verbal and non-verbal means used by TED speakers, the authors conclude that the discourse of TED Talks is polyintentional, with the predominance of the macrointention of informing. The authors note that the principle of polyintentionality underlying TED Talks allows speakers to effectively convey their ideas to the audience, motivate listeners and emphasize the importance of changes in life and education.